Electron transfer processes of coadsorbed Anthracene and N,N-Dimethylaniline on titania-silica - Anna Eremenko; Natalie Smirnova; Oksana Yakimenko; Galina Starukh; David R. Worrall; Siân L. Williams (International Journal of Photoenergy)
The effect of titania-silica binaries on the processes of PET and the decay kinetics of the Anthracene (An) fluorescence and An radical cation in presence of the co-adsorbed electron donor N,Ndimethylaniline (DMA) has been studied. The fluorescence of excited An adsorbed on pure silica is quenched by the addition of DMA, while co-adsorption of DMA on Ti/Si binaries resulted in increase of fluorescence intensity of adsorbed An. We suggest that competitive adsorption between DMA and An results in DMA occupying more active “titania” sites causing the shift of An molecules to weaker adsorption sites located on the silica support. An and DMA molecules being adsorbed simultaneously on the surface, effectively produce reduced titanium ions due to an electron transfer process. These data appear to lend weight to the suggestion of a pre-exciplex An-DMA state on the surface and effective PET from the excited molecular pair to the acceptor sites on the surface. These sites may be titania aggregates, or titania ions when there is a low content of Ti in the binaries.